Pengaruh Green Product dan Citra Perusahaan Pada Minuman Isotonik Hydro Coco Terhadap Minat Beli Konsumen (Studi Pada Pengunjung Minimarket Wilayah Surabaya Selatan) - DWI KAIMA, ARIAN; SETYO IRIANI, SRI (Jurnal Ilmu Manajemen (JIM), 2018)
Consumers nowadays aware of their rights to get a decent, secure, and environment friendly product. Consumers actually also pay attention for many information about a product company or corporate reputation at the time. This study aims to analyze the effect of Green Product and Corporate Image toward consumer purchase intention. Sample used in this study is 110 customers of minimart visitor in South Surabaya area with age start from 19 years. This study using Likert scale. Questionnaire counting as measuring tool. Data analysis using multiple linear regression equation model with SPSS 22.0 program. The results of this study showed that green product had a positive effect on the consumer purchase intention, and corporate image had a positive effect on the consumer purchase intention.